A practical review of gastrointestinal manifestations in Parkinson's disease. (June 2017) - Su, Andrew; Gandhy, Rita; Barlow, Carrolee; Triadafilopoulos, George
Abstract: Parkinson's disease (PD) is a chronic neurodegenerative disease with prominent motor and non-motor symptoms. Gastrointestinal (GI) dysfunction is among the most common and bothersome of non-motor symptoms that physicians will encounter while caring for their patients. Patients are subject to a wide variety of GI symptoms involving organs from the oropharynx to the anorectum. Our awareness and understanding of GI involvement in PD continues to evolve. In this review, we use a gastroenterologist's perspective to provide practical considerations for the diagnosis and symptom-based management of GI dysfunction seen in PD. Our aim is to assist neurologists and specialists as they encounter these symptoms while caring for the many neurologic manifestations of PD. Highlights: Review on acute and chronic gastrointestinal dysfunction in Parkinson's Disease. Provides a gastroenterologist's perspective on diagnosis and symptom-based management in Parkinson's Disease. Reviews various ancillary tests available to help with diagnosis.